A review on Role of Biofuel in India- Potential & Technology - Kumar Sharma, Vipul; Gupta, Anuj; Ahmed, Anwer; Verma, Sushant (International Journal of Engineering and Technology, 2018)
India is the 3rd energy consumer in the world, while China is the first & USA is the 2nd energy consumer. By 2021, India expected to become 3rd automobile market in the world. India is the world fastest growing developing economy in the world. Automobile industries have a multiplier effect on the country economy, health & climate change. Indian automobile sector is growing with the average of 11%. For continue economic development & minimum health hazard, the use of Biofuel for India is essential. The major sources of Biofuel in India are Jatropha, corn, vegetable oil & food grains etc. Indian government set 5% necessary blending for crude oil in the initial stage than 10% blending after that 20% blending with NBM. India became the 4th largest Biofuel producer country in the world.The aim of this review of Biofuel and its potential on carbon emission & its effect on health & climate change is to discuss. From this review, it is found that carbon emission can be reduced by Biofuel. It can be used as an alternative fuel. Government policy on Biofuel with suggestions in future use will be presented.Â Â
Keywords: Biofuel; Carbon; Energy; Emission; NBM